Rare foreign bodies of upper aerodigestive tract: a study of 30 cases - Samor, Vivek; Sarowa, Deepchand; Nayak, Pooja D.; Saini, Vaibhav; Kaur, Gagandeep; Rathi, Uma (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Aero-digestive foreign bodies are prevalent in our part of the country. Apart from the usual foreign body we encountered some unique foreign bodies, the diagnosis and management of which, is difficult due to varied and overlapping clinical presentation. Rare foreign bodies in the aero-digestive tract pose challenges in diagnosis and treatment. Methods: This was a retrospective observational study on thirty patients with aerodigestive foreign bodies who visited our hospital from July 2015 to October 2017. Results: Maximum number of cases was seen in age group of 0-5 years. The male to female ratio was 2:1. Among various types of foreign bodies, majority were metallic (43.3%). The most common site was cricopharynx (53.3%) followed by bronchus (26.6%) and esophageal (16.6%). The most common procedure done was hypopharyngoscopy (53.3%). Conclusions: Aerodigestive tract foreign bodies are one of the emergencies that have considerable mortality and morbidity. High degree of skill and suspicion are required by surgeon for the management of foreign body.